The study of galactic beat cepheids with application of its results to those in the Magellanic Clouds - Chekhonadskikh, F. A.; Kovtyukh, V. V.; Belik, S. I. (Одеські астрономічні публікації, 2014)
A thorough study of the correlation between P1=P0 ratio, fundamental period, and chemical composition (abundances of metals that compose Z) was conducted to investigate the significance of the iron-peak elements on the ratio. The results suggested a more accurate P1=P0 ratio that can be useful as an alternative means of determining a beat Cepheid’s metallicity. Metallicities for a large sample of stars were analysed using the suggested ratio. The metallicity distribution function for the Magellanic Clouds projected on the celestial sphere was constructed for the first time, and several stars with anomalous metallicities were detected. The average metallicities of the Magellanic Clouds were also obtained independently: –0.30 dex for the Large Magellanic Cloud (LMC) and –0.49 dex for the Small Magellanic Cloud (SMC). The [Fe=H] values for two newly-found bimodal Cepheids in the Galactic bulge were estimated: –0.39 dex for OGLE-BLG-CEP-03 and –0.29 dex for OGLE-BLG-CEP-21.